Investigation of Antioxidant Activity and Total Anthocyanins from Blackberry (Rubus hirtus Waldst. and Kit) and Cherry Laurel (Laurocerasus officinalis Roem) - Guder, Aytac; Korkmaz, Halil (Asian Journal of Chemistry, 2012)
In present study, water and ethanol extracts of blackberry (Rubus hirtus Waldst. and Kit) and cherry laurel (Laurocerasus officinalis Roem.) was studied for antioxidant properties. We investigated the antioxidant properties of blackberry and cherry laurel extracts by employing several in vitro antioxidant assays such as total antioxidant activity, reducing abilities, DPPH free radical, superoxide anion radical and hydrogen peroxide scavenging and ferrous ions chelating activities. In addition, total phenolic and total flavonoid contents in the both extracts of fruits were determined as gallic acid equivalent. Butylated hydroxyanisole, butylated hydroxytoluene and a-tocopherol were used as references antioxidant compounds. At the concentration of 50 μg/mL, water extracts of Rubus hirtus (WERH) and Laurocerasus officinalis (WELO) showed 75.18 and 80.96 % inhibition on peroxidation of linoleic acid emulsion, respectively. At the same concentration, ethanol extracts of Rubus hirtus (EERH) and Laurocerasus officinalis (EELO) exhibited 82.86 and 74.51 % inhibition on peroxidation of linoleic acid emulsion, respectively. On the other hand, total anthocyanins were investigated in both extracts as μg/mL cyanidin-3-glucoside (cyd-3-glu). A relationship has been found between antioxidant activity of extracts and total anthocyanins. The results acquired in the present study indicate that both extracts have more effective antioxidant capacity than synthetic and natural standard compounds.